Prevalence of pneumonia and its determinant factors among under-five children in Gamo Zone, southern Ethiopia, 2021 - Yerukneh Solomon; Zelalem Kofole; Tewodros Fantaye; Solomon Ejigu (Frontiers Media S.A., 2022)
BackgroundPneumonia, which is a form of acute lower respiratory tract infection, affects the lung parenchyma and destructs alveolar air space. Pneumonia is the leading cause of morbidity and mortality in under-five children. It was estimated that pneumonia kills 900,000 under-five children each year worldwide. Approximately 172 deaths per 1,000 live births occur in sub-Saharan African countries, with pneumonia being the major cause. This study aimed to assess the prevalence and determinant factors of pneumonia inunder-five children in southern Ethiopia.MethodologyAn institutional cross-sectional study was employed. A total of 239 child-caregiver pairs were included. Data were collected by trained nurses using a semi-structured questionnaire. The collected data were checked for completeness, coded and entered into EPI data version 4.6, and exported to SPSS version 25 for analysis. Results were reported as the mean, frequency, and percentile. Logistic regression was employed to assess statistically significant predictors of pneumonia. Variables with a p-value <0.05 were considered statistically significant factors of pneumonia.ResultThe prevalence of pneumonia in the study area was 30%. Among the factors assessed, place of food cooking-inside the living room [adjusted odd ratio (AOR) = 5.79, 95% confidence interval (CI): 2.47-13.58], nonexclusive breastfeeding (AOR = 3.26, 95% CI: 1.42-7.52), vitamin A supplementation status (AOR = 5.62, 95% CI: 2.65-11.94), and vaccination status (AOR = 3.59, 95% CI: 1.49-8.66) were significantly associated with the occurrence of pneumonia in under-five children.ConclusionThis study showed that the prevalence of pneumonia was relatively higher in Arba Minch town than other parts of the country. Place of food cooking, nonexclusive breastfeeding, vitamin A supplementation status, and vaccination status of children were significant factors of pneumonia among under-five children. Enhancing caregivers'/mothers' awareness of predicted factors was needed to reduce the incidence of childhood pneumonia and to enhance children's quality of health.